149 Reducing Complications and Improving Outcomes Following Total Hip Arthroplasty. (12th October 2021) - Al-Zubaidy, M; Monem, M; Hallett, C; Ganesh, D; Sarraf, K; Bhattacharya, R; Lewis, A
Abstract: Aim: Neck of femur (NOF) fractures are increasing, and the need to improve mobility and reduce complications whilst improving discharge time is an ongoing challenge. Hip fracture fixation and arthroplasty are essential in improving pain and mobility. NOF patients often undergo a fascia iliaca block (FIB) to improve outcomes. Guay J's Cochrane systematic review confirms that FIBs reduce pain pre and postoperatively, decrease hospital-acquired pneumonia risk and improve mobility. Patients on anticoagulants are typically refused bedside blocks, however we are unsure if they truly impact adverse outcomes in FIBs for NOF patients. Method: A retrospective observational study was undertaken to assess complication rates in 53 NOF patients who had a FIB at St Mary's Hospital between 07/01/2020 and 26/06/2020. Patients whose NOF was the result of an inpatient fall were excluded. Pre-existing anticoagulant and antiplatelet use were noted, as were the A&E admission blood coagulation results. Local complications which may have arisen post-FIB were closely screened for in documentation until the patient's discharge date. Results: There were no local complications in all 53 patients. Interestingly, one patient had a documented thigh haematoma pre-nerve block, but did not have any evolution of the haematoma and achieved good pain relief from the block. Conclusions: FIBs appear to be a safe and effective analgesic tool in the perioperative NOF patient and use has been reported to reduce early complications in those who undergo hip fracture treatment. We aim to implement these findings and increase the rate of nerve block procedures in NOF fractures.